2022
DOI: 10.1002/advs.202105113
|View full text |Cite
|
Sign up to set email alerts
|

Photomultiplication‐Type Organic Photodetectors for Near‐Infrared Sensing with High and Bias‐Independent Specific Detectivity

Abstract: Highly responsive organic photodetectors allow a plethora of applications in fields like imaging, health, security monitoring, etc. Photomultiplication‐type organic photodetectors (PM‐OPDs) are a desirable option due to their internal amplification mechanism. However, for such devices, significant gain and low dark currents are often mutually excluded since large operation voltages often induce high shot noise. Here, a fully vacuum‐processed PM‐OPD is demonstrated using trap‐assisted electron injection in BDP‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…[ 1–5 ] OPDs can be classified as photodiode type OPDs (PD‐OPDs) with external quantum efficiency (EQE) <100% and photomultiplication type OPDs (PM‐OPDs) with EQE >100% according to their working mechanism. [ 6,7 ] In light of the bandwidth of photoresponse, the OPDs can be divided into broadband and narrowband OPDs. [ 8,9 ] Broadband PD‐OPDs can be easily realized by employing active layers with wide photon‐harvesting range due to the photovoltaic effect of PD‐OPDs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] OPDs can be classified as photodiode type OPDs (PD‐OPDs) with external quantum efficiency (EQE) <100% and photomultiplication type OPDs (PM‐OPDs) with EQE >100% according to their working mechanism. [ 6,7 ] In light of the bandwidth of photoresponse, the OPDs can be divided into broadband and narrowband OPDs. [ 8,9 ] Broadband PD‐OPDs can be easily realized by employing active layers with wide photon‐harvesting range due to the photovoltaic effect of PD‐OPDs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Photomultiplication type PPDs (PM-PPDs) have emerged as the research hotspot in recent years, exhibiting the prominent advantages such as high-sensitivity, low-power consumption and tunable spectral-response-range. [4][5][6] PM-PPDs can be obtained on the basis of active layers possessing single charge carrier transport channels, which were firstly reported by Zhang's group. [7][8][9] The weight difference between the donor and the acceptor is dozens of times in active layers of PM-PPDs, which prefer to form some isolated traps for one kind of charge and also retain continuous transport channels for the opposite charge.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] More recently, photomultiplication-type (PM-type) OPDs have presented extremely high external quantum efficiency (EQE) and responsivity, which is very attractive for weak light detection without pre-amplification and could potentially overcome the conventional charge transport limited low detectivity of OPDs. [18][19][20][21][22][23] In 2008, Chen and co-workers combined CdTe nanoparticles with OPDs and realized high photoconductive gain based on the diode structure. 24 Later on, Guo et al reported multiplication-type OPDs based on interfacial trap-controlled charge injection, and achieved ultraviolet photodetectors with ultrahigh responsivity.…”
Section: Introductionmentioning
confidence: 99%